Moderately hypo-fractionated radiotherapy combined with S-1 in inoperable locally advanced esophageal squamous cell carcinoma: A prospective, single-arm phase II study (GASTO-1045) - Zhou, Rui; Luo, Guangyu; Guo, Suping; Wu, Yingjia; Luo, Qiaoting; Wang, Daquan; Chen, Naibin; Liu, Fangjie; Guo, Jinyu; Ye, Wenfeng; Qiu, Bo; Liu, Hui (Frontiers in Oncology, 2023)
Purpose: We launched this prospective phase II single-arm trial on the combination of moderately hypo-fractionated radiotherapy and S-1, to explore the safety and efficacy of the new potent regimen in inoperable locally advanced esophageal squamous carcinoma (LA-ESCC) patients. Methods: Patients with unresectable stage II-IVB LA-ESCC (UICC 2002, IVB only with metastatic celiac or supraclavicular lymph nodes) were included. Moderately hypofractionated radiotherapy (60Gy in 24 fractions) concurrent with S-1 was delivered. Meanwhile, gastrostomy tube placement by percutaneous endoscopic gastrostomy (PEG) was performed to provide nutritional support. Nutritional supplements were prescribed to meet requirements. The study outcomes included objective response rate (ORR), progression-free survival (PFS), overall survival (OS), locoregional progression-free survival (LRPFS), distant metastasis-free survival (DMFS), failure pattern, toxicities, nutritional status and treatment compliance. Endoscopy was routinely performed during post-treatment follow-up. Results: Fifty-eight patients were included with a median follow-up of 24.4 months. The median age was 63 years (range 49-83 years) and 42 patients (72.4%) had stage III or IV diseases. The ORR was 91.3% and the CR rate was 60.3%. The estimated 2-year PFS rate and 2-year OS rate was 44.2% (95% confidence interval (CI), 31.3-57.1%) and 71.4% (95% CI, 59.4-83.4%), respectively. Radiation-induced esophagitis was the most common non-hematologic toxicity and 5 patients (8.6%) developed grade≥3 esophagitis. While, with PEG nutrition support, the nutrition-related indicators presented a clear trend toward a gradual improvement. Treatment-related death was not observed. Conclusions: The moderately hypo-fractionated radiotherapy combined with S-1 showed promising loco-regional disease control and survival benefit in inoperable LA-ESCC patients. Meanwhile, favorable nutritional status and low incidence of severe radiation-induced esophagitis were observed with PEG nutritional support. Moreover, endoscopy examination contributed to the early detection of recurrent esophageal lesions and timely salvage treatment. The efficacy and toxicity of the combined regimen deserved further evaluation.